2017
DOI: 10.5603/gp.a2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Labour in women with gestational diabetes mellitus

Abstract: Objectives: Gestational diabetes mellitus (GDM) constitutes one of the most common pregnancy complications and affects 3-5% of all pregnancies, with its incidence still growing. Due to possible maternal and fetal complications, the peripartum management of GDM patients continues to be a debatable issue. The aim of the study was to analyse the course and final way of delivery in women with gestational diabetes mellitus. The effectiveness of induction of labour (IOL) was also assessed and factors predisposing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…Preterm delivery increases rate of cesarean sections. As other studies show GDM increases risk of CC instead of vaginal delivery in comparison to general population of pregnant women [16][17][18]. In our study the incidence of CC was over 70% percent in both studied groups.…”
Section: Discussionsupporting
confidence: 60%
“…Preterm delivery increases rate of cesarean sections. As other studies show GDM increases risk of CC instead of vaginal delivery in comparison to general population of pregnant women [16][17][18]. In our study the incidence of CC was over 70% percent in both studied groups.…”
Section: Discussionsupporting
confidence: 60%
“…This study concluded that, in the absence of signs of fetal distress or macrosomia, planned early birth was not indicated. Similarly, Grabowska et al [149] compared CS rates for 96 women who underwent IOL with 32 women who had a spontaneous labour and found that IOL did not increase the risk of CS (25% versus 25%, p = 0.66). A cohort study by Melamed [150] compared outcomes associated with IOL at 38 or 39 weeks and EM for 6417 women with GDM, and found that IOL at 38 or 39 weeks was associated with a lower CS rates but higher risk of NICU admission, when done at <39 weeks gestation.…”
Section: Diabetesmentioning
confidence: 99%
“…Nine studies in relation to diabetes were included, consisting of two Cochrane reviews [9,145], a secondary analysis of a trial that compared different treatments for mild gestational diabetes mellitus (GDM) [146] and six retrospective cohort studies [147][148][149][150][151][152]. With the exception of one study [145], all evaluated women with GDM, and excluded those with type I or II diabetes.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The important risk factors of GDM include advanced maternal age, obesity and a family history of type 2 diabetes (T2DM) [1,2]. This disorder is associated with several maternal and neonatal metabolic and cardiovascular complications [3,4]. Recent studies suggest that genetic factors play important role in pathogenesis of GDM [5].…”
Section: Introductionmentioning
confidence: 99%